Avaliação da ingestão protéica e do balanço e do balanço nitrogenado em universitários praticantes de musculação - Neiva, Cassiano Merussi [UNESP]; Daniel, Marcela Furlan (My University, 2010)
The alimentation of fitness people is fundamental by health. This study it has for objective to evaluate of quali-quantitative form the proteic-caloric ingestion, the nitrogen balance and its relation caloric ingestion/estimated metabolic rate, in colleges student practicing of body-building. Eleven body-builders student (18 until 30 years old), both sex, had been analyzed. The attainment of data used an alimentary register, and the gotten information were analyzed together with the nitrogen balance from 24 hours of piss collection. We observed that the nitrogen balance of individuals that make use of some protein supplement is significantly bigger than individuals that do not consume no type of it. This because, the percentile caloric obtained from protein ingestion is significantly raised, and this associate to the caloric ingestion in this group also is raised, determines the obtained results.

A alimentação de pessoas ativas é fundamental para saúde. Este estudo objetivou avaliar quali-quantitativamente a ingestão protéico-calórica, o balanço nitrogenado e a relação ingestão calórica / taxa metabólica estimada em universitários praticantes de musculação. Foram analisados 11 universitários (18 a 30 anos), ambos os sexos, praticantes de musculação. Para obtenção de dados utilizou-se anamnese de registro alimentar, e as informações obtidas foram analisadas junto ao balanço nitrogenado a partir da urina de 24 horas. Observamos que o balanço nitrogenado de indivíduos usuários de suplementação protéica é superior ao de indivíduos que não o fazem, pois, nesse caso, o percentual calórico advindo da ingestão protéica está sensivelmente elevado, e isso, dado ao fato da ingestão calórica nesse grupo também ser elevada, determina os resultados encontrados.
Keywords: Protein; Body building; Nitrogen balance; Nutritional supplements; Proteína; Musculação; Balaço nitrogenado; Suplementos nutricionais